Early Supplier Integration in Cast Product Development Partnerships – A Multiple Case Study of Environmental and Cost Effects in the German Foundry Value Chain - Robert Christian Fandl; Tobias Held; Wolfgang Kersten (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Companies have to take sustainability into consideration, nowadays. This paper analyses the impacts of environmental and cost effects on product development partnerships in the German foundry value chain. The starting point of the paper is a survey conducted in the period, end of 2012 / beginning of 2013, covering supplier and customer integration issues on the interfaces of casting houses and their clients, in which all German foundries and customers from diverse sectors of the machine-building industry have been contacted. Based on the results, the authors collected in-depth data, via semi-structured interviews, for several complex product development projects, in order to analyse how suppliers were integrated by their customers during casting development. By analysing cross-case differences, this paper explores how environmental and cost effects impact product development partnerships. It presents a multiple case study analysis, covering four new cast product development cases of one German foundry which deals with four different machine building customers. It is shown that customer-supplier relationships appear to be related to different integration practices. The results demonstrate the substantial impact of environment and cost effects on customer-supplier relationships, and help to understand how sustainable product development partnerships should be configured, while taking the particular situation into account.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; product development partnerships; supplier relationships; environmental and cost effects; foundry value chain